Physical Activity and Gut Microbiota: Implications for Metabolic Health - A Narrative Review - Muraszewska, Emilia; Łuczyński, Cezary; Muraszewski, Łukasz; Kwitowska, Patrycja; Pyjecka, Małgorzata; Ubysz, Eryk; Król, Agata; Lewandowska, Edyta; Paczkowski, Maciej; Wręczycki, Mariusz (Quality in Sport, 2026)
Background. The gut microbiota plays a key role in metabolic regulation and is increasingly recognized as a mediator of lifestyle-related health outcomes. Physical activity has emerged as a potential modulator of microbial composition and function. Aim. This narrative review aims to summarize current evidence on the relationship between physical activity and the gut microbiota and to evaluate its implications for metabolic health. Materials and Methods. A PubMed search of English-language studies published over the last 10 years was conducted to assess the effects of physical activity on the gut microbiota and metabolic health. Additional studies were identified through reference screening. Results. Regular moderate physical activity is associated with increased microbial diversity and a higher abundance of beneficial bacteria, including short-chain fatty acid producers. These changes are linked to improved glucose metabolism, reduced inflammation, and enhanced intestinal barrier function. However, excessive or prolonged high-intensity exercise may induce adverse effects, such as increased gut permeability and dysbiosis. The observed effects are strongly influenced by diet and individual factors. Conclusions. The gut microbiota represents an important mediator of exercise-induced metabolic adaptations. Combined lifestyle interventions, particularly physical activity and a fiber-rich diet, may provide synergistic benefits. Further research is needed to develop personalized strategies targeting the gut microbiota in metabolic disease prevention.